AUDIT REPORT LAG : FAKTOR – FAKTOR PENGARUH DAN DAMPAKNYA TERHADAP RESPON PASAR PADA SAHAM PERUSAHAAN MANUFAKTUR YANG BEREDAR (Studi Empiris pada Perusahaan Manufaktur Indonesia) - Fitra Rahmadi Ibrahim; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2019)
This study aims to analyze the effect of public accounting firm’s reputation, company size and extraordinary items on audit report lag and its effect on market response to outstanding shares owned by manufacturing companies in Indonesia. The sample used in this study is manufacturing companies listed on the Indonesia Stock Exchange during the period 2017 - 2018. The final number of samples are 76 samples. Research data was obtained from companies’ annual report which published on Indonesia Stock Exchange’s website and historical stock prices from yahoo finance. Determination of this sample was carried out by purposive sampling method. The research hypothesis cites using analysis of multiple regression analysis and logistic regression analysis. The results of this research indicate that public accounting firm’s reputation has no significant effect on audit report lag while firm’s size has positive effect on audit report lag. In addition, audit report lag does not give any significant effect on market response